Diagnostic Accuracy of Three Sensory Tests for Diagnosis of Sensory Disturbances - Li, Xiang-Ming; Yang, Yi; Hou, Yi; Yang, Jian-Tao; Qin, Ben-Gang; Fu, Guo; Gu, Li-Qiang (Journal of Reconstructive Microsurgery, 2015)
Background Clinical diagnosis of sensory disturbances is extremely challenging, partly because the utility of sensory tests is questionable. Transection of C7 nerve root provides an objective assessment model to determine the diagnostic accuracy of sensory tests. The purpose of this study was to investigate the diagnostic accuracy of Semmes-Weinstein Monofilaments (SWM; Sammons Preston, Bolingbrook, IL), static two-point discrimination (s2PD), and current perception threshold (CPT) tests in patients with contralateral C7 nerve root transfer.Methods The contralateral index finger of patients was tested preoperatively and 6 weeks postoperatively, including the Revised Short-Form McGill Pain Questionnaire (SF-MPQ-2), SWM, s2PD, and CPT tests. The SF-MPQ-2 was used as a gold standard for sensory disturbances.Results A total of 38 patients were included in the study. The likelihood probability ratio of SWM and CPT tests generated small shifts in probability, whereas the s2PD test did not show any capacity to detect sensory disturbances. The areas under the curves (AUC) for SWM and CPT tests were 0.724 and 0.697, respectively. Based on different positive test standards, the AUCs for s2PD (≥ 6 mm) and s2PD (≥ 7 mm) tests were 0.632 and 0.658, respectively. When CPT and SWM tests were combined as a measure, the AUC increased to 0.763.Conclusion The SWM and CPT tests show a small capacity to detect sensory disturbances, whereas the s2PD test does not show any diagnostic capacity. To better understand sensory disturbances, a comprehensive testing protocol including valid measures of physical impairment and symptom-specific measurement tools should be adopted.
Keywords: sensory disturbances; contralateral C7 nerve root transfer; sensory test